(untitled) (New York, 2011)
The 2011 Human Development Report argues that the urgent global challenges of sustainability and equity must be addressed together - and identifies policies on the national and global level that could spur mutually reinforcing progress towards these interlinked goals. Bold action is needed on both fronts, the Report contends, if the recent human development progress for most of the world's poor majority is to be sustained, for the benefit of future generations as well as for those living today. Past Reports have shown that living standards in most countries have been rising - and converging - for several decades now.
Keywords: Sustainability,Phát triển bền vững; Social aspects,Khía cạnh xã hội